2020
DOI: 10.1111/ced.14357
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of turmeric in COVID‐19

Abstract: Turmeric ( Curcuma longa L.) is an integral part of Asian culture which has been used in traditional medicine systems like Ayurveda, Unani and Siddha owing to its wide array of medicinal properties since centuries. Curcumin, the predominant curcumoid in turmeric, influences multiple signaling pathways and been found to possess anti‐inflammatory, anti‐oxidant, antimicrobial, hypoglycemic, wound healing, chemopreventive, chemosensitising and radiosensitising properties. 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 5 publications
0
38
0
3
Order By: Relevance
“…Recently, studies have suggested the repurposing of curcumin [ 180 ], glycyrrhizin [ 181 ], thymoquinone [ 182 ], and polyphenolic flavonoids [ 183 ] for COVID-19 owing to their potential to exert synergistic or additive effects including antiviral, anti-inflammatory, immunomodulatory, and antioxidant activities, with no systemic toxicity. Although, the interaction and risks appear to have negligible therapeutic concern [ 184 ].…”
Section: Pharmaceutical Preparation and Drug Interactions Of mentioning
confidence: 99%
“…Recently, studies have suggested the repurposing of curcumin [ 180 ], glycyrrhizin [ 181 ], thymoquinone [ 182 ], and polyphenolic flavonoids [ 183 ] for COVID-19 owing to their potential to exert synergistic or additive effects including antiviral, anti-inflammatory, immunomodulatory, and antioxidant activities, with no systemic toxicity. Although, the interaction and risks appear to have negligible therapeutic concern [ 184 ].…”
Section: Pharmaceutical Preparation and Drug Interactions Of mentioning
confidence: 99%
“…It is important to note the significant intersection of COVID-19 systemic manifestations and the benefits of curcumin administration noted herein, and by several others that have examined curcumin as a preventative or treatment option. [89][90][91] In every system where COVID-19 seems to manifest, including the CNS, curcumin has broad spectrum coverage of the associated inflammatory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Turmeric, a commonly used Indian condiment, has been found to contain Curcumin which has anti-inflammatory, anti-oxidant, antimicrobial, anti-viral, wound healing, chemopreventive, chemosensitising, and radiosensitising properties and is commonly used for skin lightening and wound healing in traditional Indian medicine. 13,14 Fuller's earth (Mul- Even though the traditional home remedies are useful, but many products can have various adverse effects also. Mustard oil is a commonly used home remedy for a wide variety of skin disorders but it has been known to cause contact dermatitis and irritant reactions by disrupting the skin barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from inhibition of microbes responsible for wound infections, honey has been shown to inhibit the growth of dermatophyte, Candida albicans and Propionibacterium acnes 11,12 . Turmeric, a commonly used Indian condiment, has been found to contain Curcumin which has anti‐inflammatory, anti‐oxidant, antimicrobial, anti‐viral, wound healing, chemopreventive, chemosensitising, and radiosensitising properties and is commonly used for skin lightening and wound healing in traditional Indian medicine 13,14 . Fuller's earth ( Multani mitti ) is another common home remedy used in Indian subcontinent, which is essentially a clay consisting of aluminium silicate.…”
Section: Discussionmentioning
confidence: 99%